2021
DOI: 10.3390/life11030214
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid System as Therapeutic Target of PTSD: A Systematic Review

Abstract: Post-Traumatic Stress Disorder (PTSD) is a complex disorder involving dysregulation of stress-related hormones and neurotransmitter systems. Research focused on the endocannabinoid system (eCBS) for anxiety and stress regulation, cognitive and emotional responses modulation and aversive memories extinction, leading to the hypothesis that it could represent a possible alternative treatment target for PTSD. In this systematic review, we summarize evidence about the efficacy and safety of medicinal cannabidiol (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 84 publications
(81 reference statements)
0
27
0
1
Order By: Relevance
“…These comprised 2 systematic reviews. 10,11 The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 12 flow chart of the study selection is presented in Appendix 1. Additional references of potential interest are provided in Appendix 5.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 4 more Smart Citations
“…These comprised 2 systematic reviews. 10,11 The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 12 flow chart of the study selection is presented in Appendix 1. Additional references of potential interest are provided in Appendix 5.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…Two systematic reviews 10,11 (that included a total of 1 relevant non-randomized study) were identified for inclusion in this review. No relevant health technology assessments, 11 was from 1974 to July 2020.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations